To show that the Product Rule of Logarithms works for the base 4 expression \( \log_4 16 + \log_4 4 \), we can evaluate both logarithms and check their sum against the logarithm of the product of the arguments.
Calculation:
-
First, evaluate \( \log_4 16 \): \[ \log_4 16 = \log_4 (4^2) = 2 \]
-
Next, evaluate \( \log_4 4 \): \[ \log_4 4 = 1 \]
-
Now, add the two results: \[ \log_4 16 + \log_4 4 = 2 + 1 = 3 \]
-
Finally, check if this sum equals \( \log_4 (16 \cdot 4) = \log_4 64 \): \[ 16 \cdot 4 = 64 \] \[ \log_4 64 = \log_4 (4^3) = 3 \]
Conclusion:
Thus, we have shown that \( \log_4 16 + \log_4 4 = \log_4 64 \), which validates the Product Rule for logarithms in this case.
Correct Option:
The response that fits this explanation is: Evaluate both \( \log_4 16 \) and \( \log_4 4 \) and show that their sum is equal to the value of \( \log_4 64 \).